Freedom and secretiveness, in late modernism - Bocheński, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The text considers two metaphors describing creative freedom in modern society: secretiveness and shadow. In the shadow, creative individuals protect themselves against the ubiquitous need to explain and screen life. The text proves that contemporary literature (Sebald, Quinard) and essay (Vuarnet, Maffesoli) search inspiration in secretiveness and shadow while at the same time they see a threat to art in the mechanism of explanation.